Science Reference Service: An Introduction for the General Reference Librarian - Not applicable (Issues in Science and Technology Librarianship, 1993)
The STS Section is sponsoring a Preconference before the ALA Annual Meeting. This Preconference is designed for academic librarians who serve at general reference desks at community colleges, colleges, or universities and who do not have formal training in science bibliography. This Preconference may also attract paraprofessionals and public librarians who answer science reference questions. All those who cringe when patrons ask sci/tech reference questions, who have gaps in their knowledge of sci/tech reference sources, who regret not taking a science reference course in library school, or who could benefit from a refresher course will find value in this Preconference.